Comparing heritage speakers and late L2-learners of European Portuguese: verb movement, VP ellipsis and adverb placement - Santos, Ana Lúcia (2016)
This study compares the performance of Portuguese-German heritage children and adult L2 speakers of European Portuguese whose L1 is German with respect to two aspects of grammar, adverb placement and VP-ellipsis, which depend on a core syntactic property of the language, verb movement. The results show that both groups have acquired V-to-I and adverb placement, showing no influence of a V2 grammar. Performance in the VP-ellipsis task is more complex: heritage children produce VP-ellipsis at the level of controls, as opposed to L2 speakers; however, both L2 and heritage speakers show that crosslinguistic influence may produce a preference for pronoun substitution over VP-ellipsis in a task asking for redundancy resolution. Nevertheless, given that overall results show that heritage children perform at the level of L1 children, we take our results to support approaches to heritage bilingualism which suggest the development of an intact grammar in childhood.